THE EMERGENCE OF A TRAGIC HERO: A Narrative Analysis of Chinua Achebe's Things Fall Apart - MARIANINGSIH, Irma (2012)
The study entitled "THE EMERGENCE OF A TRAGIC HERO: A NARRATIVE ANALYSIS OF CHINUA ACHEBE'S THINGS FALL APART" is aimed to investigate the way a tragic hero emerged in the novel. The data were collected from the novel in the forms of words, phrases, and sentences. Utilizing textual analysis in describing the collected data, the present study adopted Bakhtin's (2004) theory as its major theoretical framework and narrative theories (Rimmon-Kenan, 1983; Bal, 1997) to support the analysis. Following Bakhtin's concept of historical novel, the findings showed that the hero's emergence is related to the historical context. The coming of the Missionaries had a great impact to the emergence of the tragic hero. From the relationship between the hero and the Missionaries, a concept of binary opposition and dualism which is wilderness/civilization and irrational/rational opposition is showed. Thus, it is concluded that the emergence of a tragic hero in Things Fall Apart, has brought a meaning of tragedy to a concept of dualism that lies between the primitive Nigerian tribes as oppose to the western civilization.